Decriminalization of Drugs and the Support for Free Markets in the United States (Journal of Advanced Research in Social Sciences, 2022)
For nearly 250 years, Americans have been able to ponder on their relatively short, but extensive ideological history. The United States was founded upon a number of ideals, but arguably the most predominant and preceding has been freedom. Heavily influenced by the Enlightenment, the U.S. founders laid the propositions protecting natural rights, while limiting governmental authority to retract upon these so-called “God-given rights.” The country’s roots lie in classical liberalism, and free markets have been an integral mechanism since 1776, through the championing of private property rights and economic freedom. However, since the War on Drugs, political discourse has distorted our historical vision and validated governmental coercion in criminalizing drug consumption and production whether that was for personal pleasure or legitimate medical reasons. The paper investigates this conflict of ideology and principle through the analysis of literature and survey data. The quantitative analysis revealed a negative relationship between support for free markets and drug decriminalization. The findings imply a substantial role of two-party politics in the U.S. in determining political beliefs outside of a clear ideology particularly related to issues like the War on Drugs.